The Influence of Final Waste Processing Site (TPA) on Land Use Change Patterns and the Socioeconomic Conditions of Communities Surrounding Medan City - Apriani Apriani; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
The existence of Final Waste Processing Sites (TPA) in urban areas often presents a dilemma between the need for waste management infrastructure and its environmental and social impacts on surrounding communities. This study aims to examine the impact of the TPA Terjun in Medan City on patterns of land use change and the socioeconomic conditions of nearby residents. The method used is quantitative, involving a survey of 150 respondents, and multiple linear regression analysis to test the influence of two independent variables namely, the characteristics of the TPA and public perception and response on community perceptions of environmental impacts. The results indicate that both independent variables have a significant simultaneous effect on public perception, with a model significance value of 0.022. Partially, the physical characteristics of the TPA have a significantly positive influence, while community perceptions and responses also contribute meaningfully. However, the low coefficient of determination (R² = 0.009) suggests that many other factors outside the model also influence perceptions of environmental impact. This study highlights the importance of a holistic approach in spatial planning and urban environmental management, particularly in relation to public facilities such as TPAs. Community participation, infrastructure quality, and zoning certainty are crucial factors in maintaining the balance between the functional needs of the city and the desired quality of the microenvironment.